Resin composition for laser welding
By introducing an aromatic polycarbonate resin composition with end group ester groups and metal compounds into the resin, the problem of insufficient connection strength of resin components in the prior art is solved, and a laser welding effect with high transparency and high strength is achieved.
Patent Information
- Application Number
- JP2023117811
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-30
AI Technical Summary
In the prior art, the method of using adhesives and occlusion structures has problems of complexity in operation and insufficient bonding strength when connecting transparent resin components, especially in parts with large weight or complex structures, which are difficult to achieve high-strength laser welding.
Using a laser welding composition containing an aromatic polycarbonate resin, the welding strength and transparency are improved by introducing end-group ester groups into the resin, combining metal compounds and antioxidants.
It realizes high transparency and high strength laser welding, suitable for connection of resin components in complex structures, and improves welding strength and reliability.
Smart Images

Figure 2025014880000001 
Figure 2025014880000002 
Figure 2025014880000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laser weldable resin composition, a laser weldable member, and a laser welded article. [Background technology]
[0002] Polycarbonate resin is an amorphous transparent resin that has excellent impact strength, heat resistance, dimensional stability, etc., and is widely used as a material suitable for automobiles, electrical parts, exterior applications, etc. Recently, there has been an increase in the use of two resin members made of polycarbonate resin bonded together in parts made of transparent and non-transparent materials, such as headlamps, and exterior parts that require design.
[0003] Examples of such joining methods include using an adhesive, using an interlocking structure, and joining (welding) the resin that constitutes the components by melting it with heat or the like. However, methods that use adhesives require complicated work, and methods that use interlocking structures are not suitable for applications that involve contact with liquids. Although welding is a simple method, the joining strength between the two resin components is not necessarily high, and in recent years, as parts have become lighter, larger, and more complex, there has been a demand for higher welding strength.
[0004] Patent Document 1 describes a vehicle lamp that uses a polycarbonate resin lens, a body made of ABS resin, and a reflector made of polyethylene terephthalate resin or polybutylene terephthalate resin, and integrates these by laser welding. However, this invention aims to suppress the occurrence of stress cracks in the body by tilting the direction of the laser light irradiation, and does not consider improving the resin material itself to increase the welding strength. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2002-292741 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object (object) of the present invention is to provide a laser weldable resin composition, a laser weldable member, and a laser welded article that have a high degree of transparency and enable strong laser welding. [Means for solving the problem]
[0007] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that a laser welding resin composition containing an aromatic polycarbonate resin having a terminal structure containing an ester group can solve the above-mentioned problems, and have arrived at the present invention. The present invention relates to the following laser weldable resin composition, laser weldable member, and laser welded article.
[0008] 1. A laser weldable resin composition comprising an aromatic polycarbonate resin (A) having a terminal structure containing an ester group. 2. The resin composition according to the above item 1, further comprising a transparent thermoplastic resin (B) other than the aromatic polycarbonate resin (A). 3. The resin composition according to the above item 2, wherein the content ratio of the aromatic polycarbonate resin (A) to the other transparent thermoplastic resin (B) is 10 to 100 mass % for (A) and 90 to 0 mass % for (B). 4. The resin composition according to the above item 1, further comprising 0.000001 to 0.05 parts by mass of a metal boride or a tungsten oxide per 100 parts by mass of the total of the aromatic polycarbonate resin (A) and the transparent thermoplastic resin (B). 5. The resin composition according to the above item 1, further comprising 0.005 to 0.5 parts by mass of a phosphite-based antioxidant per 100 parts by mass in total of the aromatic polycarbonate resin (A) and the transparent thermoplastic resin (B). 6. A laser weldable member comprising the resin composition according to any one of 1 to 5 above. 7. A laser welding member as described in 6 above, which is for use as a laser light transmitting member. 8. The laser weldable member according to 7 above, having a haze of 20% or less at a thickness of 2 mm. 9. A laser welded body in which the laser light transmitting member according to 7 above is laser welded to a laser light absorbing member. 10. The laser welded product according to 9 above, wherein the width of the laser welded portion is 0.5 to 10 mm. Effect of the Invention
[0009] The laser weldable resin composition of the present invention has a high degree of transparency and can provide a laser weldable member that can be firmly laser welded. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the present invention will be described in detail with reference to embodiments and examples, but the present invention should not be construed as being limited to the embodiments and examples shown below. In this specification, unless otherwise specified, the symbol "to" is used to mean that the numerical values before and after it are included as the lower limit and upper limit.
[0011] The laser weldable resin composition of the present invention is characterized by containing an aromatic polycarbonate resin having a terminal structure containing an ester group.
[0012] [Aromatic polycarbonate resin (A) having a terminal structure containing an ester group] The laser weldable resin composition of the present invention contains an aromatic polycarbonate resin (A) having an end structure containing an ester group. The aromatic polycarbonate resin (A) having an end structure containing an ester group has a low glass transition temperature, which improves laser weldability and makes it possible to achieve high laser weld strength. The terminal structure containing an ester group is not particularly limited as long as it contains an ester structure, but is preferably a group consisting of a combination of an ester group and a hydrocarbon group, or a combination of an ester group, a hydrocarbon group, and -O-.
[0013] The terminal structure containing an ester group preferably has a terminal structure represented by the following formula (1): By using an aromatic polycarbonate resin having a terminal structure containing an ester group represented by formula (1), the glass transition temperature of the aromatic polycarbonate resin can be lowered.
[0014] [ka] In formula (1), R 1 R represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 30 carbon atoms. 2 each independently represents a halogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms. n represents an integer of 0 to 4. * represents a bonding site to another site.
[0015] R 1 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 30 carbon atoms, preferably an alkyl group or alkenyl group having 10 or more carbon atoms, more preferably an alkyl group or alkenyl group having 12 or more carbon atoms, and even more preferably an alkyl group or alkenyl group having 14 or more carbon atoms. 1 is preferably an alkyl or alkenyl group having 22 or less carbon atoms, and more preferably an alkyl or alkenyl group having 18 or less carbon atoms. R 1 is preferably an alkyl group. The alkyl group and alkenyl group are preferably linear or branched alkyl or alkenyl groups, and more preferably linear alkyl or alkenyl groups. R 1 is preferably a hexadecyl ester or a 2-hexyldecyl ester, and particularly preferably a hexadecyl group. Also, R 1 may be located at any of the meta, para, or ortho positions, but is preferably located at the meta or para position, and more preferably at the para position.
[0016] R 2 each independently represents a halogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms, and is preferably a fluorine atom, a chlorine atom, a methyl group, an ethyl group, or a phenyl group, and more preferably a fluorine atom, a chlorine atom, or a methyl group. n represents an integer of 0 to 4, preferably an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0.
[0017] The terminal structure represented by formula (1) can be added to an aromatic polycarbonate resin by using an end-capping agent such as parahydroxybenzoic acid hexadecyl ester.
[0018] Among the terminal structures represented by formula (1), it is particularly preferable to have either a parahydroxybenzoic acid hexadecyl ester structure or a parahydroxybenzoic acid 2-hexyldecyl ester structure, or both. The aromatic polycarbonate resin having the terminal structure represented by formula (1) may have one type of terminal structure represented by formula (1) or two or more types of terminal structures represented by formula (1).
[0019] The aromatic polycarbonate resin (A) having a terminal structure containing an ester group may be used in combination with a terminal terminator having another structure. It is preferable that 80 mol % or more of the total terminal terminators used have the structure represented by the above formula (1), more preferably 90 mol % or more of the total terminal terminators used have the structure represented by the above formula (1), and particularly preferably that all the terminal terminators used have the structure represented by the above formula (1).
[0020] Other examples of the end terminator that may be used in combination include alkylphenols such as phenol, p-cresol, o-cresol, 2,4-xylenol, pt-butylphenol, o-allylphenol, p-allylphenol, p-hydroxystyrene, p-hydroxy-α-methylstyrene, p-propylphenol, p-cumylphenol, p-phenylphenol, o-phenylphenol, p-trifluoromethylphenol, p-nonylphenol, p-dodecylphenol, eugenol, amylphenol, hexylphenol, heptylphenol, octylphenol, nonylphenol, decylphenol, dodecylphenol, myristylphenol, palmitylphenol, stearylphenol, and behenylphenol, and alkyl esters of parahydroxybenzoic acid such as methyl ester, ethyl ester, propyl ester, butyl ester, amyl ester, hexyl ester, and heptyl ester. It is also possible to use two or more of the above monohydric phenols in combination.
[0021] The aromatic polycarbonate resin (A) having a terminal structure containing an ester group is preferably a bisphenol type polycarbonate resin, more preferably a bisphenol A type polycarbonate resin. In addition, it is preferable that 50 mol % or more of the bisphenol type polycarbonate resin has at least one terminal structure represented by formula (1). When the aromatic polycarbonate resin has a terminal structure represented by formula (1), the terminal structure preferably consists solely of the terminal structure represented by formula (1).
[0022] The bisphenol A polycarbonate resin may also have other structural units than the carbonate structural units derived from bisphenol A and its derivatives. In the bisphenol polycarbonate resin, the carbonate structural units derived from bisphenol A and its derivatives preferably account for 90% by mass or more, more preferably 95% by mass or more, and even more preferably 97% by mass or more of all structural units excluding terminal structures.
[0023] Examples of dihydroxy compounds constituting such other structural units include the following aromatic dihydroxy compounds.
[0024] Bis(4-hydroxyphenyl)methane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 2,2-bis(4-hydroxyphenyl)-4-methylpentane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3-(1-methylethyl)phenyl)propane, 2,2-bis(4-hydroxy-3-tert-butylphenyl)propane, 2,2-bis(4-hydroxy -3-(1-methylpropyl)phenyl)propane, 2,2-bis(4-hydroxy-3-cyclohexylphenyl)propane, 2,2-bis(4-hydroxy-3-phenylphenyl)propane, 1,1-bis(4-hydroxyphenyl)decane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxydiphenyl)phenylmethane, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3, 5-dimethylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-(1-methylethyl)phenyl)cyclohexane, 1,1-bis(4-hydroxy-3-tert-butylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-(1-methylpropyl)phenyl)cyclohexane, 1,1-bis(4-hydroxy-3-cyclohexylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-phenylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-methylphenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3-(1-methylethyl)phenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3-tert-butylphenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3-(1-methylpropyl)phenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3-cyclohexylphenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3-phenylphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclooctane, 4,4'-(1,3-phenylenediisopropylidene)bisphenol, 4,4'-(1,4-phenylenediisopropylidene)bisphenol, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 4,4'-dihydroxybenzophenone, 4,4'-dihydroxyphenyl ether, 4,4'-dihydroxybiphenyl, 1,1-bis(4-hydroxyphenyl)-3,3-5-trimethylcyclohexane, 1,1-bis(4-hydroxy-6-methyl-3-tert-butylphenyl)butane.
[0025] The method for producing the bisphenol A type polycarbonate resin is not particularly limited, and examples thereof include known methods such as an interfacial polymerization method and a melt transesterification method.
[0026] The viscosity average molecular weight (Mv) of the aromatic polycarbonate resin (A) having a terminal structure containing an ester group is not particularly limited, but is preferably 14000 or more, more preferably 16000 or more, and particularly preferably 18000 or more, 19000 or more, and particularly preferably 20000 or more, and is preferably 36000 or less, and particularly preferably 34000 or less, 32000 or less, and particularly preferably 28000 or less. By setting the viscosity average molecular weight (Mv) to be equal to or more than the lower limit and equal to or less than the upper limit, the laser weldability tends to be improved. In addition, aromatic polycarbonate resins (A) having a terminal structure containing two or more types of ester groups with different viscosity average molecular weights may be mixed and used. In this case, aromatic polycarbonate resins (A) having a terminal structure containing an ester group with a viscosity average molecular weight outside the above range may be mixed to adjust the viscosity average molecular weight within the above range.
[0027] In this specification, the viscosity average molecular weight (Mv) of a polycarbonate resin is calculated by determining the intrinsic viscosity [η] (unit: dl / g) at a temperature of 25°C using methylene chloride as a solvent and an Ubbelohde viscometer, and calculating the viscosity average molecular weight (Mv) from the Schnell viscosity formula, i.e., η = 1.23 × 10 -4 Mv 0.83 The intrinsic viscosity [η] is the value calculated from the specific viscosity [η sp ] was measured and the value was calculated according to the following formula.
number
[0028] The glass transition temperature of the aromatic polycarbonate resin (A) having a terminal structure containing an ester group is preferably 140° C. or less, more preferably 139° C. or less, even more preferably 135° C. or less, may be 132° C. or less, and may even be 125° C. or less. The glass transition temperature of the aromatic polycarbonate resin (A) having a terminal structure containing an ester group is preferably 121° C. or more, more preferably 122° C. or more, and even more preferably 123° C. or more. By setting the glass transition temperature to be equal to or less than the upper limit and equal to or more than the lower limit, the laser weldability tends to be further improved.
[0029] The glass transition temperature is measured in accordance with JIS K7122 using a differential scanning calorimeter (DSC, specifically, "DSC7020" manufactured by Hitachi High-Tech Science Corporation) with a measurement starting temperature of 25°C, a heating rate of 10°C / min, a final temperature of 300°C, and a heating rate of 5°C / min, with two cycles of heating and cooling.
[0030] [Transparent thermoplastic resin (B)] Furthermore, the resin composition of the present invention preferably contains a transparent thermoplastic resin (B) other than the aromatic polycarbonate resin (A) having a terminal structure containing an ester group. Such transparent thermoplastic resin (B) is not particularly limited, and examples thereof include thermoplastic resins such as polycarbonate resins other than the aromatic polycarbonate resin (A); acrylic resins such as polymethyl methacrylate resin; amorphous polyester resins such as polyethylene terephthalate (PET) resin; polystyrene-based resins; cyclic polyolefin-based resins; and vinyl chloride resins, or polymer alloys consisting of two or more of these thermoplastic resins. Among these, from the viewpoint of transparency, it is preferable to use a polycarbonate resin (B1) other than the aromatic polycarbonate resin (A) or an acrylic resin (B2), and a polycarbonate resin other than the aromatic polycarbonate resin (A) is particularly preferable. As the transparent thermoplastic resin (B), a resin having a haze value of 20% or less when measured using the transparent thermoplastic resin (B) by the method described in the examples is preferable.
[0031] <Polycarbonate resin (B1)> The polycarbonate resin (B1) is not limited as long as it is a polycarbonate resin other than the above-mentioned aromatic polycarbonate resin (A), and examples thereof include aromatic polycarbonate resins, aliphatic polycarbonate resins, and aromatic-aliphatic polycarbonate resins. Preferably, it is an aromatic polycarbonate resin, and specifically, an aromatic polycarbonate polymer or copolymer obtained by reacting an aromatic dihydroxy compound with phosgene or a diester of carbonic acid is used.
[0032] As the aromatic dihydroxy compound, those exemplified in the aromatic polycarbonate resin (A) having a terminal structure containing an ester group or other aromatic dihydroxy compounds can be used. Preferable aromatic dihydroxy compounds include, in particular, 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A), 2,2-bis(3-methyl-4-hydroxyphenyl)propane (i.e., bisphenol C), tetramethylbisphenol A, α,α'-bis(4-hydroxyphenyl)-p-diisopropylbenzene, hydroquinone, resorcinol, 4,4'-dihydroxydiphenyl, and the like.
[0033] Preferred examples of the polycarbonate resin (B1) include polycarbonate resins using bisphenol A as a dihydroxy compound or a combination of bisphenol A and other aromatic dihydroxy compounds, and polycarbonate resins using bisphenol C or a combination of bisphenol C and other aromatic dihydroxy compounds (particularly bisphenol A).
[0034] The polycarbonate resin (B1) may be a homopolymer consisting of one type of repeating unit, or a copolymer having two or more types of repeating units, in which case the copolymer may be selected from various copolymer forms such as a random copolymer, a block copolymer, etc. The method for producing the aromatic polycarbonate resin (B1) is not particularly limited, and may be a conventional method such as a phosgene method (interfacial polymerization method) or a melting method (ester exchange method).
[0035] The molecular weight of the polycarbonate resin is arbitrary and may be appropriately selected and determined, but the viscosity average molecular weight (Mv) is usually 10,000 or more, preferably 14,000 or more, more preferably 16,000 or more, and usually 40,000 or less, preferably 28,000 or less. By setting the viscosity average molecular weight to the lower limit of the above range or more, the mechanical strength of the resin composition can be further improved, and the destruction of the base material of the laser welded molded body can be suppressed, which is more preferable when used for applications requiring high mechanical strength. On the other hand, by setting the viscosity average molecular weight to the upper limit of the above range or less, the decrease in the flowability of the resin composition can be suppressed and improved, and the molding processability can be improved, making it easier to perform molding process. Two or more polycarbonate resins having different viscosity average molecular weights may be mixed and used. In this case, a polycarbonate resin having a viscosity average molecular weight outside the above preferred range may be mixed to adjust the viscosity average molecular weight within the above range.
[0036] The polycarbonate resin (B1) may be not only virgin raw materials, but also polycarbonate resin regenerated from used products (so-called material recycled polycarbonate resin), or polycarbonate resin produced from a polycarbonate resin chemically decomposed back to its raw materials (so-called chemically recycled polycarbonate resin), and it is also preferable that it contains both virgin raw materials and recycled resin, or it may be made of recycled polycarbonate resin. When using recycled polycarbonate resin, the proportion of recycled polycarbonate resin in polycarbonate resin (B1) is preferably 40% or more, 50% or more, 60% or more, or 80% or more, and may be 100%. Preferred examples of used products include various sheets, optical recording media such as optical disks (CDs, DVDs), light guide plates, transparent vehicle components such as automobile window glass, automobile headlamp lenses, and windshields, containers such as water bottles, various covers, eyeglass lenses, soundproof walls, glass windows, corrugated sheets, and other building components. In addition, as recycled polycarbonate resins, crushed products obtained from non-conforming products, sprues, or runners during molding, or pellets obtained by melting these can also be used.
[0037] <Acrylic resin (B2)> The acrylic resin (B2) is preferably a methyl (meth)acrylate-based resin, and the monomer amount of the structural unit of methyl (meth)acrylate is preferably 80 mol% or more, preferably 90 mol% or more, based on the total monomer amount of all structural units. The acrylic resin is also preferably a copolymer of methyl (meth)acrylate with other methyl (meth)acrylate, ethyl acrylate, butyl acrylate, or the like. Examples of such copolymers include copolymers of methyl (meth)acrylate and a (meth)acrylate compound having an aromatic compound in the side chain, specifically phenyl methacrylate-methyl methacrylate-methyl acrylate copolymer and 4-phenylbenzyl methacrylate-methyl methacrylate-methyl acrylate copolymer. In this specification, unless otherwise specified, "(meth)acrylate" refers to both or either of acrylate and methacrylate.
[0038] The acrylic resin (B2) preferably has a mass average molecular weight of 5,000 or more, more preferably 8,000 or more, further preferably from 20,000 to 200,000, and particularly preferably from 50,000 to 150,000. The mass average molecular weight of the acrylic resin (B2) is a value measured by gel permeation chromatography using standard polystyrene as a standard sample.
[0039] The methods for producing the acrylic resin (B2) are generally roughly classified into emulsion polymerization, suspension polymerization, and continuous polymerization, and the acrylic resin used in the present invention is preferably an acrylic resin produced by a continuous polymerization method. Furthermore, the continuous polymerization method can be further classified into a continuous bulk polymerization method and a continuous solution polymerization method, and the acrylic resin produced by any of the methods can be used in the present invention. The acrylic resin (B2) may be used alone or in combination of two or more kinds.
[0040] As described above, the transparent thermoplastic resin (B) is preferably a polycarbonate resin (B1) or an acrylic resin (B2). However, when the transparent thermoplastic resin (B) contains a thermoplastic resin other than a polycarbonate resin or an acrylic resin, the content thereof is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and particularly preferably 3 parts by mass or less, per 100 parts by mass of the polycarbonate resin (B1) or the acrylic resin (B2).
[0041] In the case where an aromatic polycarbonate resin (A) having an end structure containing an ester group and another transparent thermoplastic resin (B) are contained, the content ratio of (A) in the resin composition is preferably 10 to 100 mass%, and (B) is preferably 90 to 0 mass%, more preferably 15 mass% or more of (A), even more preferably 20 mass% or more, 25 mass% or more, and particularly preferably 30 mass% or more. The polycarbonate resin (A) may be 100 mass% or 95 mass% or less, and is also preferably 90 mass% or less, 85 mass% or less, 80 mass% or less, 75 mass% or less, or 70 mass% or less.
[0042] The resin composition for laser welding of the present invention may contain a laser beam absorbent, which is preferably a compound capable of absorbing light with a wavelength of 900 to 1200 nm. Examples of such compounds include inorganic compounds such as metal borides and tungsten oxides, and organic compounds such as cyanine dyes, squarium dyes, quinone compounds, and azo compounds, as well as metal complexes such as phthalocyanine metal complexes, naphthalocyanine metal complexes, dithiol metal complexes, phenylenediamine complexes, and nickel dithiolene complexes, each of which contains a metal such as aluminum, zinc, or vanadium. These laser ray absorbents can be used alone or in combination of two or more. The content of the laser beam absorbent is preferably 0.000001 to 0.1 part by mass per 100 parts by mass of the total of the aromatic polycarbonate resin (A) and the transparent thermoplastic resin (B).
[0043] [Metal borides, tungsten oxides] The resin composition for laser welding of the present invention preferably contains a metal boride and / or a tungsten oxide as a laser light absorbent. The metal boride is preferably at least one metal boride selected from the group consisting of La, Ce, Pr, Nd, Tb, Dy, Ho, Y, Sm, Eu, Er, Tm, Yb, Lu, Sr, and Ca, and the tungsten-based oxide is preferably at least one tungsten-based oxide selected from potassium tungsten oxide, rubidium tungsten oxide, cesium tungsten oxide, and thallium tungsten oxide.
[0044] Metal borides are compounds that absorb light in the wavelength range of laser light, and have a large number of free electrons to generate plasma resonance vibration. When laser light is incident on a metal boride, the free electrons are excited according to the frequency of the light, causing collective vibration of the electrons, which absorb and radiate energy. The absorption wavelength at this time depends on the density of free electrons and the energy structure of the particles, and has a plasma absorption wavelength in the vicinity of the 800-1200 nm wavelength range of Nd:YAG lasers and semiconductor laser light.
[0045] The metal boride is preferably represented by the general formula XB6 (wherein X is one or more metal elements selected from La, Ce, Pr, Nd, Tb, Dy, Ho, Y, Sm, Eu, Er, Tm, Yb, Lu, Sr and Ca), and XB4, XB 12 The borides may contain small amounts of other borides represented by the formula (I) and the like. Of the above, La and Ce are preferable as X, and LaB6 and CeB6 are more preferable because of their outstanding absorbency and transparency, with LaB6 being particularly preferable.
[0046] The metal boride is preferably in the form of fine particles, and the average dispersed particle size is preferably 200 nm or less, more preferably 100 nm or less, and even more preferably 85 nm or less. The lower limit is not particularly limited, but for example, 1 nm or more is preferable because it is easy to produce industrially. The average dispersed particle size can be measured by a particle size measuring device based on the dynamic light scattering method, and the median value (D 50 ).
[0047] The tungsten oxide is preferably selected from potassium tungsten oxide, rubidium tungsten oxide, cesium tungsten oxide and thallium tungsten oxide. By adding potassium, rubidium, cesium and thallium elements M to tungsten oxide WO3 to form a composite tungsten oxide, free electrons are generated in WO3, and strong absorption characteristics derived from the free electrons are expressed particularly in the near infrared region, making it effective as a laser light absorbing compound with a wavelength of around 1000 nm. When the composite tungsten oxide is expressed as MxWyOz (wherein M is potassium, rubidium, cesium or thallium, W is tungsten, and O is oxygen), a composite tungsten oxide that satisfies the relationships 0.01≦x / y≦1 and 2.0≦z / y≦3 is more preferable.
[0048] The tungsten oxide is preferably in the form of fine particles, and the average dispersed particle size is preferably 200 nm or less, more preferably 100 nm or less, and even more preferably 85 nm or less. The lower limit is not particularly limited, but for example, 1 nm or more is preferable because it is easy to produce industrially. Here, the average dispersed particle size can be measured by a particle size measuring device based on the dynamic light scattering method, and is the median value (D 50 ).
[0049] The content of the metal boride or tungsten oxide in the case where it is contained is preferably 0.000001 to 0.5 parts by mass relative to 100 parts by mass of the total of the aromatic polycarbonate resin (A) and the transparent thermoplastic resin (B). By setting the content at such a level, the transparency and laser weldability become good. The content is preferably 0.000002 parts by mass or more, more preferably 0.000003 parts by mass or more, and even more preferably 0.000004 parts by mass or more, among which 0.000005 parts by mass or more, particularly preferably 0.0001 parts by mass or more, and preferably 0.4 parts by mass or less, more preferably 0.3 parts by mass or less, among which 0.2 parts by mass or less, 0.1 parts by mass or less, 0.05 parts by mass or less, 0.03 parts by mass or less, particularly preferably 0.02 parts by mass or less. The preferred amount in the case where the metal boride and the tungsten oxide are both contained is also this amount.
[0050] Basically, when a laser beam absorbent is contained in the laser beam absorbing side member during laser welding, the laser beam is absorbed, generating heat and melting the laser beam absorbing side member, and the laser beam transmitting side member (the member irradiated with laser beam) also melts due to heat transfer, and both members are solidified and welded together. However, the above-mentioned compounds having the ability to absorb light with wavelengths of 900 to 1200 nm are highly transparent laser beam absorbents, and the resin composition of the present invention is also a material with excellent transparency. Therefore, by containing these compounds in the laser beam transmitting side member (the member irradiated with laser beam) made of the resin composition of the present invention, the laser beam transmitting side member melts more easily, stronger laser welding can be achieved, and a laser welded body with excellent transparency can be obtained. The laser-absorbent side member may contain carbon black within the range not impairing the object of the present invention.
[0051] [Phosphite-based antioxidants] It is also preferable that the laser weldable resin composition of the present invention further contains a phosphite-based antioxidant. The phosphite compound is a trivalent phosphorus compound represented by the general formula: P(OR)3, where R represents a monovalent or divalent organic group.
[0052] Examples of such phosphite compounds include triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyldiphenyl phosphite, dioctyl monophenyl phosphite, monodecyldiphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, distearyl pentaerythritol diphosphite, bis(2,4- di-tert-butyl-4-methylphenyl)pentaerythritol phosphite, bis(2,6-di-tert-butylphenyl)octyl phosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene-diphosphite, 6-[3-(3-tert-butyl-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]-dioxaphosphepine, and the like.
[0053] Among such phosphite compounds, aromatic phosphite compounds represented by the following formula (2) or the following formula (3) having a spiro ring skeleton are more preferred.
[0054] [ka] [In formula (2), R1 , R 2 and R 3 may be the same or different and represent an aryl group having 6 to 30 carbon atoms.
[0055] [ka] [In formula (3), R 4 and R 5 may be the same or different and represent an aryl group having 6 to 30 carbon atoms.
[0056] As the phosphite-based antioxidant represented by the above formula (2), triphenyl phosphite, tris(mononylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, etc. are preferred, and tris(2,4-di-tert-butylphenyl) phosphite is more preferred. Specific examples of such phosphite-based antioxidants include "Adeka STAB 1178" manufactured by ADEKA Corporation, "Sumilizer TNP" manufactured by Sumitomo Chemical Co., Ltd., "JP-351" manufactured by Johoku Chemical Industry Co., Ltd., "Adeka STAB 2112" manufactured by ADEKA Corporation, "Irgafos 168" manufactured by BASF, and "JP-650" manufactured by Johoku Chemical Industry Co., Ltd.
[0057] As the phosphite-based antioxidant represented by the above formula (3), those having a pentaerythritol diphosphite structure such as bis(2,4-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are particularly preferred. Specific examples of such phosphite-based antioxidants include "ADEKA STAB PEP-36" manufactured by ADEKA Corporation and "Doverphos S-9228" manufactured by Doverchemical Co., Ltd.
[0058] The phosphite antioxidant may be contained alone or in any combination and ratio of two or more kinds.
[0059] The content of the phosphite antioxidant is preferably 0.005 to 0.5 parts by mass, preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and also preferably 0.4 parts by mass or less, further preferably 0.3 parts by mass or less, among which 0.2 parts by mass or less, 0.1 parts by mass or less, and particularly preferably 0.05 parts by mass or less, based on 100 parts by mass of the total of the aromatic polycarbonate resin (A) and the transparent thermoplastic resin (B). By including such an amount, it is possible to further improve excellent color tone (haze), heat discoloration resistance, and wet heat discoloration resistance.
[0060] [Alkyl acid phosphates, their metal salts, organic phosphonic acids] The laser weldable resin composition of the present invention also preferably contains an alkyl acid phosphate or a metal salt thereof, or an organic phosphonic acid.
[0061] The alkyl acid phosphate is preferably one represented by the following formula (4). O=P(OH) n (OR) 3-n …(4) [In formula (4), R is an alkyl group having 9 to 30 carbon atoms, and n is an integer of 1 or 2. When n is 1, the two Rs may be the same or different.] The alkyl acid phosphate is preferably represented by the above formula (4), and the alkyl acid phosphate metal salt is preferably a metal salt such as a zinc salt or an aluminum salt of the alkyl acid phosphate represented by the above formula (4).
[0062] The alkyl group represented by R in the above formula (4) may be a straight-chain alkyl group or may be branched. Specific examples of the alkyl group represented by R include nonyl, isononyl, decyl, isodecyl, dodecyl, tridecyl, isotridecyl, tetradecyl, hexadecyl, octadecyl (i.e., stearyl), eicosyl, and tetracosyl groups. The number of carbon atoms in the alkyl group is more preferably 13, 18, or 24, and the alkyl acid phosphate is particularly preferably a mixture of distearyl acid phosphate (n=1) and monostearyl acid phosphate (n=2).
[0063] As the metal salt of alkyl acid phosphate, a mixture of distearyl acid phosphate zinc salt (n=1) and monostearyl acid phosphate zinc salt (n=1) is particularly preferred.
[0064] The organic phosphonic acid is preferably one represented by the following formula (5). RP(=O)(OH)2…(5) [In formula (5), R is a group selected from the group consisting of an aryl group, an aralkyl group, and an alkyl group.] In the above formula (5), the aryl group includes, for example, phenol, hydroxyphenyl, naphthyl, etc., the aralkyl group includes, for example, benzyl, p-hydroxybenzyl, 4-hydroxy-2,5-di-t-butylbenzyl, etc., and the alkyl group includes, for example, ethyl, propyl, butyl, hexyl, octyl, etc.
[0065] Specific preferred examples of the organic phosphonic acid include phenylphosphonic acid, tolylphosphonic acid, benzylphosphonic acid, p-hydroxybenzylphosphonic acid, 4-hydroxy-3,5-di-t-butylbenzylphosphonic acid, ethylphosphonic acid, etc. Among these, arylphosphonic acids such as phenylphosphonic acid are preferred.
[0066] When alkyl acid phosphate, its metal salt, or organic phosphonic acid is contained, the content is preferably 0.00007 to 0.1 parts by mass relative to 100 parts by mass of the total of the aromatic polycarbonate resin (A) and the transparent thermoplastic resin (B). By containing such an amount, the resin composition, welding member, and welded body of the present invention can provide a laser welding member that has high transparency and excellent heat (humid heat) discoloration resistance and can be firmly laser welded, and the welded body by laser welding can have excellent transparency and excellent heat discoloration resistance and moist heat discoloration resistance. The content is preferably 0.0001 parts by mass or more, particularly 0.0005 parts by mass or more, particularly 0.001 parts by mass or more, preferably 0.08 parts by mass or less, and more preferably 0.07 parts by mass or less.
[0067] [Release agent] The laser welding resin composition of the present invention preferably contains a release agent (lubricant). Examples of the release agent include aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, and polysiloxane-based silicone oils.
[0068] Examples of the aliphatic carboxylic acid include saturated or unsaturated aliphatic mono-, di- or tri-carboxylic acids. Here, the aliphatic carboxylic acid also includes alicyclic carboxylic acids. Among these, preferred aliphatic carboxylic acids are mono- or di-carboxylic acids having 6 to 36 carbon atoms, and more preferred are saturated aliphatic mono-carboxylic acids having 6 to 36 carbon atoms. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, and azelaic acid.
[0069] The aliphatic carboxylic acid in the ester of aliphatic carboxylic acid and alcohol can be, for example, the same as the aliphatic carboxylic acid. On the other hand, the alcohol can be, for example, a saturated or unsaturated monohydric or polyhydric alcohol. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, a monohydric or polyhydric saturated alcohol having 30 or less carbon atoms is preferred, and an aliphatic saturated monohydric alcohol or an aliphatic saturated polyhydric alcohol having 30 or less carbon atoms is more preferred. Here, the term aliphatic is used to include alicyclic compounds.
[0070] Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol.
[0071] The above ester may contain an aliphatic carboxylic acid and / or alcohol as an impurity. The above ester may be a pure substance, or may be a mixture of a plurality of compounds. The aliphatic carboxylic acid and alcohol that are combined to form an ester may each be used alone or in any combination and ratio of two or more.
[0072] Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture containing myricyl palmitate as a main component), stearate stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, and pentaerythritol tetrastearate.
[0073] Examples of aliphatic hydrocarbons having a number average molecular weight of 200 to 15,000 include liquid paraffin, paraffin wax, microwax, polyethylene wax, Fischer-Tropsch wax, and α-olefin oligomers having 3 to 12 carbon atoms. The aliphatic hydrocarbons also include alicyclic hydrocarbons. These hydrocarbons may be partially oxidized. Among these, paraffin wax, polyethylene wax, or a partial oxide of polyethylene wax is preferred, and paraffin wax and polyethylene wax are more preferred. The number average molecular weight of the aliphatic hydrocarbon is preferably 5,000 or less. The aliphatic hydrocarbon may be a single substance, but a mixture of substances having various constituent components and molecular weights can also be used as long as the main component is within the above range.
[0074] Examples of polysiloxane-based silicone oils include dimethyl silicone oil, methylphenyl silicone oil, diphenyl silicone oil, and fluorinated alkyl silicone oil.
[0075] The above-mentioned release agents may be contained alone or in any combination and ratio of two or more kinds.
[0076] The content of the release agent is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, and usually 2 parts by mass or less, preferably 1 part by mass or less, based on 100 parts by mass of the total of the aromatic polycarbonate resin (A) and the transparent thermoplastic resin (B). If the content of the release agent is less than the lower limit of the above range, the effect of releasability may be insufficient, whereas if the content of the release agent is more than the upper limit of the above range, there is a possibility that a decrease in hydrolysis resistance and mold contamination during injection molding may occur.
[0077] [Ultraviolet absorber] It is also preferable that the laser weldable resin composition of the present invention further contains an ultraviolet absorber. Examples of the ultraviolet absorber include inorganic ultraviolet absorbers such as cerium oxide and zinc oxide; and organic ultraviolet absorbers such as benzotriazole compounds, benzophenone compounds, salicylate compounds, cyanoacrylate compounds, triazine compounds, oxanilide compounds, malonic acid ester compounds, and hindered amine compounds. Among these, organic ultraviolet absorbers are preferred, and benzotriazole compounds are more preferred. By selecting an organic ultraviolet absorber, the transparency and mechanical properties of the resin composition of the present invention can be improved.
[0078] Specific examples of the benzotriazole compound include, for example, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-[2'-hydroxy-3',5'-bis(α,α-dimethylbenzyl)phenyl]-benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-5-chlorobenzotriazole, and 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-5-chlorobenzotriazole. t-amyl)-benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol] and the like. Among these, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole and 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol] are preferred, and 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole is particularly preferred. Specific examples of such benzotriazole compounds include "Seesorb 701", "Seesorb 705", "Seesorb 703", "Seesorb 702", "Seesorb 704", and "Seesorb 709" manufactured by Shipro Chemical Co., Ltd., "Biosorb 520", "Biosorb 582", "Biosorb 580", and "Biosorb 583" manufactured by Kyodo Pharmaceutical Co., Ltd., "Chemisorb 71" and "Chemisorb 72" manufactured by Chemipro Chemical Co., Ltd., "Cyasorb UV5411" manufactured by Cytec Industries, "LA-32", "LA-38", "LA-36", "LA-34", and "LA-31" manufactured by ADEKA, and "Tinuvin P", "Tinuvin 234", "Tinuvin 326", "Tinuvin 327", and "Tinuvin 328" manufactured by BASF.
[0079] Specific examples of the benzophenone compound include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-n-dodecyloxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2,2'-dihydroxy-4-methoxybenzophenone, and 2,2'-dihydroxy-4,4'-dimethoxybenzophenone. Specific examples of such benzophenone compounds include Seesorb 100, Seesorb 101, and Seesorb 201 manufactured by Shipro Chemical Co., Ltd. Examples of such compounds include "Seesorb 101S", "Seesorb 102", and "Seesorb 103" manufactured by Kyodo Pharmaceutical Co., Ltd., "Biosorb 100", "Biosorb 110", and "Biosorb 130" manufactured by Chemipro Kasei Co., Ltd., "Chemisorb 10", "Chemisorb 11", "Chemisorb 11S", "Chemisorb 12", "Chemisorb 13", and "Chemisorb 111" manufactured by BASF, "Ubinur 400" manufactured by BASF, "Ubinur M-40" manufactured by BASF, "Ubinur MS-40" manufactured by BASF, "Cyasorb UV9", "Cyasorb UV284", "Cyasorb UV531", and "Cyasorb UV24" manufactured by Cytec Industries, and "ADK STAB 1413" and "ADK STAB LA-51" manufactured by ADEKA.
[0080] Specific examples of salicylate compounds include phenyl salicylate, 4-tert-butylphenyl salicylate, etc., and specific examples of such salicylate compounds include "Seesorb 201" and "Seesorb 202" manufactured by Shipro Chemical Co., Ltd., and "Chemisorb 21" and "Chemisorb 22" manufactured by Chemipro Chemical Co., Ltd.
[0081] Specific examples of cyanoacrylate compounds include ethyl-2-cyano-3,3-diphenylacrylate, 2-ethylhexyl-2-cyano-3,3-diphenylacrylate, and the like. Specific examples of such cyanoacrylate compounds include "Seesorb 501" manufactured by Shipro Chemical Co., Ltd., "Biosorb 910" manufactured by Kyodo Pharmaceutical Co., Ltd., "Ubisolator 300" manufactured by Daiichi Chemical Co., Ltd., "Ubinur N-35" and "Ubinur N-539" manufactured by BASF, and the like.
[0082] A specific example of the oxalinide compound is 2-ethoxy-2'-ethyl oxalinic acid bis-arylidine. A specific example of such an oxalinide compound is "Sandubor VSU" manufactured by Clariant.
[0083] As the malonic acid ester compound, 2-(alkylidene)malonic acid esters are preferable, and 2-(1-arylalkylidene)malonic acid esters are more preferable. Specific examples of such malonic acid ester compounds include "PR-25" manufactured by Clariant Japan and "B-CAP" manufactured by BASF.
[0084] When the laser welding resin composition of the present invention contains an ultraviolet absorbing agent, the content thereof is usually 0.05 parts by mass or more, preferably 0.1 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, based on 100 parts by mass of the total of the aromatic polycarbonate resin (A) and the transparent thermoplastic resin (B). If the content of the ultraviolet absorbing agent is less than the lower limit of the above range, the effect of improving weather resistance may be insufficient, and if the content of the ultraviolet absorbing agent is more than the upper limit of the above range, mold deposits and the like may occur, causing mold contamination. The ultraviolet absorbing agent may be contained alone or in any combination and ratio of two or more kinds.
[0085] [Other ingredients] The resin composition for laser welding of the present invention may contain other components in addition to those described above, as necessary, as long as the desired physical properties are not significantly impaired. Examples of other components include various resin additives, other resins, etc. Note that the other components may be contained alone or in any combination and ratio of two or more.
[0086] <Resin additives> Examples of resin additives include flame retardants, flame retardant auxiliaries, fillers, fluorescent whitening agents, impact resistance improvers, antistatic agents, antifogging agents, antiblocking agents, flow improvers, plasticizers, dispersants, compatibilizers, antibacterial agents, etc. The resin additives may be contained alone or in any combination and ratio of two or more. Examples of the filler include fibrous or granular fillers such as glass fibers. When the difference in refractive index between the glass fiber and the resin composition is preferably less than 0.01, and more preferably less than 0.005 at a wavelength of 550 nm, the transparency of the laser weldable member is excellent. In addition to the above-mentioned components, other resins, additives, etc. may be contained as necessary, so long as the desired physical properties are not significantly impaired.
[0087] <Other resins> Other resins include, for example, thermoplastic polyester resins such as polyethylene terephthalate resin, polytrimethylene terephthalate resin, and polybutylene terephthalate resin; styrene-based resins such as polystyrene resin, high impact polystyrene resin (HIPS), acrylonitrile-styrene copolymer (AS resin), acrylonitrile-styrene-acrylic rubber copolymer (ASA resin), and acrylonitrile-ethylene propylene rubber-styrene copolymer (AES resin); polyolefin resins such as polyethylene resin and polypropylene resin; polyamide resins; polyimide resins; polyetherimide resins; polyurethane resins; polyphenylene ether resins; polyphenylene sulfide resins; and polysulfone resins. The other resins may be contained either alone or in any combination and ratio of two or more kinds. However, when other resins are contained, the content thereof is preferably 20 parts by mass or less per 100 parts by mass of the total (A) of the aromatic polycarbonate resin (A) and the transparent thermoplastic resin (B), more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and particularly preferably 3 parts by mass or less.
[0088] [Production of resin composition] There is no limitation on the method for producing the laser weldable resin composition of the present invention, and a wide variety of known methods for producing resin compositions can be used. Specific examples include a method in which the above-mentioned essential components and other components to be added as necessary are mixed in advance using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded with a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, a kneader, etc. In this case, it is also preferable to side-feed each component as necessary.
[0089] In addition, for example, the laser weldable resin composition can be produced by not mixing the components in advance, or by mixing only some of the components in advance, feeding the mixture to an extruder using a feeder, and melt-kneading the mixture. In addition, for example, a resin composition obtained by premixing some of the components, feeding the mixture to an extruder, and melt-kneading the mixture to obtain a master batch can be produced by mixing the master batch again with the remaining components and melt-kneading the mixture to produce a laser welding resin composition. In addition, the master batch can be mixed with resin pellets as a base material and directly charged into a molding machine to produce a molded body. In addition, for example, when mixing a component that is difficult to disperse, the component that is difficult to disperse can be dissolved or dispersed in a solvent such as water or an organic solvent in advance, and then kneaded with the solution or dispersion to improve dispersibility.
[0090] [Molded body] The laser weldable resin composition of the present invention is molded into a laser weldable member. The molding method can be any molding method generally used for thermoplastic resin compositions. Examples of the molding method include injection molding, ultra-high speed injection molding, injection compression molding, two-color molding, gas-assisted hollow molding, molding using a heat-insulating mold, molding using a rapid heating mold, foam molding (including supercritical fluid), insert molding, IMC (in-mold coating molding) molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, etc. Also, a molding method using a hot runner system can be used. Among these, injection molding methods such as injection molding, ultra-high speed injection molding, and injection compression molding, sheet extrusion molding, and profile extrusion molding are preferred.
[0091] The molded article made from the resin composition of the present invention is used as a laser welding component, particularly preferably as a laser beam transmitting component, for laser welding. The laser weldable member molded using the resin composition for laser welding of the present invention has a transmittance at a wavelength of 1070 nm measured at a thickness of 2 mm according to ISO13468-2 of preferably 99% or less, more preferably 97% or less, particularly preferably 95% or less, and also preferably 70% or more, particularly preferably 80% or more. Specific details of the method for measuring the transmittance are as described in the Examples.
[0092] The haze of the laser welding member is preferably 20% or less, more preferably 10% or less, even more preferably 5% or less, and particularly preferably 1% or less, as measured at a thickness of 2 mm using a turbidimeter based on JIS K7136 and JIS K7361. Specific details of the method for measuring the haze are as described in the Examples.
[0093] The shape of the molded article to be used by molding the resin composition for laser welding of the present invention is not limited, and may be a flat plate or a non-planar shape such as a curved shape, for example, a dome shape, a hemisphere shape, a cylinder shape, a pyramid shape, a corrugated plate shape, or a complex shape combining planar and non-planar shapes.
[0094] The method of laser welding is not particularly limited and can be performed by a normal method. Preferably, the laser welding member obtained from the resin composition for laser welding of the present invention is used as the laser light transmitting side member (laser light irradiated side member), and is brought into face contact or butt contact with the laser light absorbing side member as the counterpart material, and pressure is applied, and the laser light is irradiated from the transmitting side member side to weld and integrate both members to form a laser welded body.
[0095] Examples of the laser light absorbing side member of the counterpart material include thermoplastic resins such as polycarbonate resins, acrylic resins such as polymethyl methacrylate resins, amorphous polyester resins such as polyethylene terephthalate resins and polybutylene terephthalate resins, polystyrene resins, ABS resins, cyclic polyolefin resins, and vinyl chloride resins, or polymer alloys made of two or more of these thermoplastic resins. Among these, polycarbonate resins are particularly preferred. From the viewpoint of compatibility, it is preferred to use a material mainly made of the same type of thermoplastic resin as the laser light transmitting side member (laser light irradiated side member).
[0096] The type of laser light irradiated in laser welding may be any near-infrared laser light, and preferred examples include a YAG (yttrium aluminum garnet crystal) laser (wavelength 1064 nm) and an LD (laser diode) laser (wavelengths 808 nm, 840 nm, 940 nm).
[0097] The welded body integrated by laser welding may have any shape, size, thickness, etc., and is suitable as a component for products that require a high degree of transparency, such as parts for wearable devices, medical device parts, optical components, lighting equipment, lenses, lens covers, various displays, electric and electronic devices, laptops, pachinko, pachislot, amusement equipment such as games, office automation equipment, information terminal equipment, home appliances, vehicle parts (lights, interior components, panels), transparent partitions, panel components such as product displays, partition boards for vending machines, ticket machines, etc., signs, watches, accessories, etc. EXAMPLES
[0098] The present invention will be described in more detail below with reference to examples, but the present invention should not be construed as being limited to the following examples. The components used in the examples and comparative examples are as shown in Table 1 below.
[0099] [Table 1]
[0100] (Examples 1 to 6, Comparative Example 1) [Production of resin pellets (A-1) and (A-2) for laser light absorbing side members] Among the components listed in Table 1 above, the components listed in Table 2 below were blended in the ratios (parts by mass) listed in Table 2, mixed in a tumbler mixer for 20 minutes, and then fed to a twin-screw extruder "TEX25αIII" manufactured by Japan Steel Works, Ltd., kneaded under conditions of a screw rotation speed of 200 rpm, a discharge rate of 25 kg / hr, and a cylinder temperature of 280°C, and extruded in a strand shape from the tip of the extrusion nozzle. The extrudate was quenched in a water tank and cut and pelletized using a pelletizer to obtain resin pellets (A-1) and (A-2) for the laser light absorbing side member.
[0101] [Production of resin pellets for laser light transmitting members] Among the components shown in Table 1 above, the components shown in Table 3 below were blended in the ratios (parts by mass) shown in Table 3, mixed in a tumbler mixer for 20 minutes, and then fed to a twin-screw extruder "TEX25αIII" manufactured by Japan Steel Works, Ltd., kneaded under conditions of a screw rotation speed of 200 rpm, a discharge rate of 25 kg / hr, and a cylinder temperature of 280°C, and extruded in a strand shape from the tip of the extrusion nozzle. The extrudate was quenched in a water tank and cut and pelletized using a pelletizer to obtain resin pellets for the laser light transmission side member.
[0102] [Transmittance at 1070 nm (2 mmt, unit: %)] The pellets obtained above were dried at 120°C for 5 hours, and then an injection molding machine ("EC-50" manufactured by Nissei Plastic Industrial Co., Ltd.) was used to manufacture a 90 mm x 60 mm three-tiered plate (1 mmt, 2 mmt, 3 mmt thickness) at a cylinder temperature of 280°C and a mold temperature of 80°C. Using an ultraviolet-visible-near infrared spectrophotometer (Shimadzu Corporation, "UV-3600"), the transmittance (unit: %) at a wavelength of 1070 nm was determined in a 2 mm thick section of the three-tiered plate in accordance with ISO13468-2.
[0103] [Haze (2mmt, unit:%)] The haze (unit: %) of a 2 mm thick section of the three-tiered plate obtained by the above method was measured using a turbidity meter ("NDH-4000" manufactured by Nippon Denshoku Industries Co., Ltd.) under a D65 light source and a 10° visual field in accordance with JIS K7136 and JIS K7361.
[0104] [Evaluation of laser weldability (welding strength)] The pellets for the laser light transmitting side member obtained above were dried at 120°C for 5 hours, and then a 1.5 mm thick, 60 mm x 30 mm test piece (laser light transmitting side member) was manufactured using an injection molding machine ("J55" manufactured by Japan Steel Works, Ltd.) under conditions of a cylinder temperature of 280°C and a mold temperature of 80°C.
[0105] In addition, the resin pellets (A-1) and (A-2) for the laser-beam-absorbing side members were used as counterpart materials, and 1.5 mm thick, 60 mm x 30 mm (laser-beam-absorbing side members A-1 and A-2) were manufactured in the same manner as above.
[0106] The obtained laser-transmitting member and laser-absorbing member were used, and their ends were overlapped so that the overlapping portion measured 20 mm×30 mm, and the overlapping portion was irradiated with laser light for laser welding. Laser welding was performed using a Panasonic galvano scanning laser processing machine VL-W1 under the following conditions: laser wavelength 1070 nm, laser output 66 W, laser scan speed 150 mm / sec, pressure 0.4 MPa, and weld size 1.6 mm x 6 mm. A tensile testing machine (Instron "5544") was used to grip the ends of the welded laser-light-transmitting member and the laser-light-absorbing member opposite the welded portion, and a load was applied in the tensile direction at a tensile speed of 5 mm / min to measure the breaking strength of the welded portion (unit: N).
[0107] The results are shown in Table 3 below.
[0108] [Table 2]
[0109] [Table 3]
[0110] (Examples 7 to 9, Comparative Example 2) [Production of resin pellets (B) for the laser light absorbing side component] Among the components shown in Table 1, the components shown in Table 4 below were blended in the ratios (parts by mass) shown in Table 4, and resin pellets (B) for the laser-light-absorbing side member were obtained in the same manner as in the production of the resin pellets for the laser-light-transmitting side member described above. The transmittance at 1070 nm (2 mmt, unit: %) and the haze (2 mmt, unit: %) were measured in the same manner as above.
[0111] [Production of resin pellets for laser light transmitting members] Among the components listed in Table 1, the components listed in Table 5 below were blended in the ratios (parts by mass) listed in Table 5, and resin pellets for the laser light transmitting side member were obtained in the same manner as in the production of the resin pellets for the laser light transmitting side member described above. The transmittance at 1070 nm (2 mmt, unit: %) and the haze (2 mmt, unit: %) were measured in the same manner as above.
[0112] [Evaluation of laser weldability] The pellets for the laser light transmitting side member obtained above were dried at 120°C for 5 hours, and then a 1.5 mm thick, 60 mm x 30 mm test piece (laser light transmitting side member) was manufactured using an injection molding machine ("J55" manufactured by Japan Steel Works, Ltd.) under conditions of a cylinder temperature of 280°C and a mold temperature of 80°C. Moreover, using the resin pellets (B) for the laser-beam-absorbing member as the counterpart material, a 1.5 mm-thick, 60 mm×30 mm (laser-beam-absorbing member) was produced in the same manner as above.
[0113] The laser-transmitting member and the laser-absorbing member thus obtained were stacked together and laser-welded in the same manner as described above. The breaking strength (unit: N) of the welded portion was measured in the same manner as above.
[0114] [Table 4]
[0115] [Table 5] [Industrial Applicability]
[0116] An article welded by laser welding the laser weldable resin composition of the present invention exhibits excellent transparency and excellent weld strength, and can therefore be suitably used as parts for various applications.
Claims
1. A laser weldable resin composition comprising an aromatic polycarbonate resin (A) having a terminal structure containing an ester group.
2. The resin composition according to claim 1, further comprising a transparent thermoplastic resin (B) other than the aromatic polycarbonate resin (A).
3. The resin composition according to claim 2, wherein the content ratio of the aromatic polycarbonate resin (A) to the other transparent thermoplastic resin (B) is 10 to 100 mass% for (A) and 90 to 0 mass% for (B).
4. The resin composition according to claim 1, further comprising 0.000001 to 0.05 parts by mass of a metal boride or a tungsten-based oxide per 100 parts by mass of the total of the aromatic polycarbonate resin (A) and the transparent thermoplastic resin (B).
5. The resin composition according to claim 1, further comprising 0.005 to 0.5 parts by mass of a phosphite-based antioxidant per 100 parts by mass of the total of the aromatic polycarbonate resin (A) and the transparent thermoplastic resin (B).
6. A laser weldable member comprising the resin composition according to any one of claims 1 to 5.
7. The member for laser welding according to claim 6 , which is for a laser beam transmitting member.
8. 8. The laser weldable member according to claim 7, which has a haze of 20% or less at a thickness of 2 mm.
9. 8. A laser welded body obtained by laser welding the laser-transmitting member according to claim 7 to a laser-absorbing member.
10. 10. The laser welded product according to claim 9, wherein the width of the laser welded portion is 0.5 to 10 mm.
Citation Information
Patent Citations
Laser welding method for lighting fixture for vehicle
JP2002292741A